COMPARATIVE ANALYSIS OF EFFICACY OF URETERAL REIMPLANTATION AT VESICOURETERAL REFLUX AND URETEROVESICAL JUNCTION OBSTRUCTION USING VESICOSCOPIC APPROACH IN CHILDREN - A. V. Pirogov; V. V. Sizonov (Вестник урологии)
Rationale. Implementation of vesicoscopic (transvesical, pneumovesicoscopic) approach (VA) in the treatment of abnormalities and diseases of vesico-ureteral junction and a urinary bladder as alternative to the open surgery makes it relevant to study efficacy of such approach in the treatment of vesicoureteral reflux (VUR) and ureterovesical junction obstruction (UVJO).Aim. To study efficacy of vesicoscopic reimplantation in vesicoureteral reflux and ureterovesical junction obstruction.Materials and methods. From April, 2013 to July 2017 we carried out vesicoscopic surgery in 134 patients with VUR (177 ureters) and 24 patients with UVJO (25 ureters), 158 children at the age of 2 months-18 years in total. To determine indications to the surgery USI, excretory urography, retrograde voiding cystourethrography were used.Results. Average duration of the surgery with use of VA in all patients was 128.6±50.0 min, in patients with VUR - 121.6±44.1 min, that slightly less than in children with UVJO – 168.9±62.4 min. Duration of postoperative period was 6.3±2.4 days, in the VUR group – 5.9±2.1 days, in the UVJO group – 8.1±3.1days. In patients with VUR reflux was repaired in 131 patients (97.7 %), in the UVJO group obstruction was eliminated in 23 patients (95.8%). Postoperative complications developed in 25 cases (15.8%) and assessed according to Clavien-Dindo classification. Relapses developed in 3 patients from the VUR group and in 1 patient from the UVJO group. We had to use conversion in 3 (1.8%) cases: once in the UVJO group (4.1%) and twice - in the VUR group (1.5%).Conclusions. In the VUR group the percent of complications was significantly lower than in the UVJO group, that may be due to older age of the patients with reflux and as a result due to large bladder volume and space for surgeon manipulation. Total efficacy of the procedure is comparable to the results of the open surgery in both groups. But the percent of complications remains enough high, especially in the group with obstruction in the area of UVJ, that may be due to younger age of the patients in such category and, as a result, due to lesser bladder volume.